Employer branding and its influence of employee retention: a literature review - Abdul Rahman, Azura; Yazid Esa, Nawal Esa; Ahmad, Nurul Afiqah (2024)
The impact of employer branding on employee retention is essential for organizations aiming to create a strong and sustainable workforce. This literature review aims to examine the role of employer branding on employee retention in the organizations. By synthesizing and analyzing a wide range of studies published between 2019 and 2023, this review provides insights into the key determinants of employee retention, identifies gaps in the literature, and offers implications for practice and future research. The articles were screened, filtered and followed by the reading of the full-text articles. From the previous results, most studies applied a quantitative approach which is the most popular research method. Therefore, this study suggests that employer branding studies should be given adequate concentration. The findings highlight the importance of various factors, including dimension of employer branding such as perceived organizational support, development value, work environment, and social value, in influencing employee retention. Furthermore, this literature review recommends that researchers should investigate and focus more on the influence of employer branding on employee retention.